Representaciones sociales sobre el psicólogo en profesores de la educación básica pública y privada de lima (costa) y provincias (sierra y selva) - Orellana Manrique, Oswaldo (2008)
Is a descriptive research using a qualitative and ethnographic study examines the social representations of the psychologist in the teachers of basic education, especially secondary schools, working in public and private institutions of Peru The variety of responses from teachers set a range of images that characterize the psychologist as a professional specializing in mental health, its sensitivity in differentiating was working with the community, with certain trends in Lima (Costa) and the Sierra and Selva. Social representation of teachers from the coast tends to recognize the psychologist with the following characteristics: on the coast: Research Specialist, Psychotherapist and Counselor in the mountains: Promoting awareness and Welfare, and the jungle: Promoter of Happiness Image and Ethics.